Retrofitting of ETFE roofs - Beccarelli, Paolo; Maffei, Roberto (2017)
ETFE is one of the most stable chemical compounds and its films are largely employed in the building industry due to the very good long-term stability, resistance to soiling and high light transmittance. The mechanical strength is relatively good, especially considering that the material is not reinforced by a woven support, and make ETFE foils suitable for load bearing envelopes characterised by small spans or supported by cables [1].